Progressive lung disease in a malt-worker. Issue 7 (July 1981) - Ellis, M E; Friend, J A
Abstract : We described a malt-worker whose initial symptoms suggested extrinsic allergic alveolitis. The ensuing cavitating lung disease, Aspergillus fumigatus infection with mycetomata, vigorous immune response, and granulomatous liver disease are unusual features.